A historical overview of turkey’s international immigration policy - Polat, Yeliz (Rating Academy, 2021)
Being influenced by political, economic and social transformations taking place in the light of national and international developments, International immigration policy in Turkey restructures. The work in this context, the aims of this article are to be examined of transformation of international immigration policy applied in Turkey in the historical process, and to be intended to reveal of the periodic change in the immigration policy. International immigration policy of Turkey has been resolved taking into account legal, institutional, socio-cultural, housing and economic dimensions in a holistic and descriptive manner, with data obtained by the methods which are literature review and reading of legislation.

Türkiye’deki uluslararası göç politikası, ulusal ve uluslararası gelişmeler ışığında yaşanan siyasal, ekonomik ve sosyal dönüşümlerden etkilenerek yeniden yapılanmaktadır. Bu bağlamda çalışmada, Türkiye’nin, uluslararası göç politikasının tarihsel süreç içinde ele alınarak irdelenmesi ve yaşanan dönüşüm ışığında bu göç politikasındaki dönemsel değişimlerin ortaya çıkarılması amaçlanmaktadır. Yazın taraması ve mevzuat okuması tekniğiyle elde edilen veriler ışığında Türkiye’nin uluslararası göç politikası, yasal, kurumsal, sosyo-kültürel, iskân ve ekonomik boyutlar dikkate alınarak bütüncül ve betimleyici bir biçimde çözümlenmiştir
Türkiye’nin uluslararası göç politikasına tarihsel bir bakış